Gadolinium-doped ceria nanopowders synthesized by urea-based homogeneous co-precipitation (UBHP) - Accardo, G.; Spiridigliozzi, L.; Cioffi, R.; Ferone, C.; Di Bartolomeo, E.; Yoon, Sung Pil; Dell'Agli, G. (ELSEVIER SCIENCE SA, 2017)
Gadolinium (10%)-doped ceria was successfully synthesized by using an urea-based co-precipitation method (UBHP). A single fluorite phase was obtained after a low temperature (400 degrees C) calcination treatment. The resulting powders showed grains of nanometric size with some agglomerations and an overall good sinterability. Pellets were sintered at 1300 and 1500 degrees C for 3 h. The ionic conductivity was measured by electrochemical impedance spectroscopy measurements and a correlation between electrical properties and microstructure was revealed. The promising conductivity values showed that the synthesized powders are suitable for intermediate temperature solid oxide fuel cells (IT-SOFCs) applications. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: OXIDE FUEL-CELL; ELECTROCHEMICAL PROPERTIES; SINTERING BEHAVIOR; PRECIPITATION; CONDUCTIVITY; ZIRCONIA; POWDER; ANODE